An Analysis of Research Trends in Brain-based Learning in Adult Education and HRD Fields: The Content Analysis and Network Text Analysis - Chang Sung Jang; Doo Hun Lim; Jieun Yoo; Jeong-ha Yim (Adult Education Research Conference, 2019)
The purpose of this study is to address the trends of the research on brain-based learning and to present an integrative theoretical framework to provide new insights and future directions in adult education and HRD fields. Based on the neuroscientific perspective, the implications of which the ways to conceptually broaden educational research and practice were discussed.
Keywords: Brain-Based Learning; Research Trends; Content Analysis; Network Text Analysis